THE EFFECT OF USING MCCARTHY’S STRATEGY TO TEACH TRIPLE JUMP IN COGNITIVE ACHIEVEMENT, PERFORMANCE, AND SELF-CONFIDENCE FOR STUDENTS OF PHYSICAL EDUCATION COLLEGE - Muhammed, Ahmed Qasim; Ibrahim, Ibrahim Musa (Journal of Duhok University, 2018)
The research objective to know the effect of using McCarthy’s strategy to teach triple jump in cognitive a achievement, performance and self- confidence for student of Physical Education College. The research sample consist of (40) students between second grade’s students in Physical Education College for the studying year 2016-2017, which divided in to two groups, each group consist of (20) students experimental group which been taught by McCarthy’s strategy and control group which taught by traditional strategy, using the design of equivalent groups with post-test. The study found statistical significant differences at the level of significance (0.05) between the average scores of the experimental group and average scores of control group in cognitive a achievement, performance and self- confidence favor of experimental group which is taught according to McCarthy’s strategy.